اتجاهات معلمي التعليم العام نحو الطلبة الموهوبين ذوي صعوبات التعلم بمنطقة جازان - حكمي، ياسر بن محسن بن محمد; عابد، مهند بن غازي (مؤسسة التربية الخاصة والتأهيل, 2023)
هدفت الدراسة الحالية إلى التعرف على اتجاهات معلمي التعليم العام نحو الطلبة الموهوبين ذوي صعوبات التعلم، وعلاقتها ببعض المتغيرات بمنطقة جازان. اتبعت الدراسة المنهج المختلط، وطبقت الاستبانة، والمقابلات كأداة لجمع البيانات. تكون مجتمع الدراسة من معلمي التعليم العام بالمدارس التي بها برامج صعوبات التعلم والموهوبين بمنطقة جازان، تكونت عينة الدراسة من (268) معلمًا، (165) ذكور (103) إناث، بينما كان عدد المشاركين في المقابلات (4) معلمين، ومن أهم نتائج الدراسة أن اتجاهات معلمي التعليم العام نحو الطلبة الموهوبين ذوي صعوبات التعلم إيجابي، وعدم وجود فروق ذات دلالة إحصائية في اتجاهات معلمي التعليم العام نحو الطلبة الموهبين ذوي صعوبات التعلم تبعًا لمتغير (المؤهل العلمي- الجنس- سنوات الخبرة- الدورات التدريبية)، وجود بعض المشكلات التي تواجه أفراد العينة، وتتمثل في عدم توفر معلمين مختصين في الموهبة. ومن أهم توصيات الدراسة إضافة محتوى عن الموهوبين ذوي صعوبات التعلم في برامج إعداد معلمي التعليم العام في الجامعات، وإعداد معلمين ومعلمات مؤهلين على قدر من المعرفة بالموهوبين ذوي صعوبات التعلم. Purpose: The current study aimed to determine General Education Teachers' attitudes towards Gifted Students with Learning Disabilities and their Relationship to Some Variables in the Jazan Region. Method: A mixed approach was used in this study. A questionnaire and interviews were used as tools for data collection. The study population consisted of general education teachers in schools with learning difficulties programs and gifted people in the Jazan region, the study sample consisted of (268) teachers, (165) males (103) females, while the number of participants in interviews was (4) teachers. Results: The attitudes of general education teachers towards gifted students with learning disabilities are positive, and there are no statistically significant differences in the attitudes of general education teachers towards gifted students with learning disabilities according to a variable (educational qualification - gender - years of experience - training course. the lack of teachers specialized in talent was the main problem. Conclusion: One of the most important recommendations of the study is to add content on gifted with learning disabilities students in the programs for preparing teachers of general education in universities, and to prepare qualified teachers with a degree of knowledge of gifted people with learning disabilities.
Keywords: المعاقون الموهوبين -- صعوبات التعلم -- استراتيجيات التعلم -- التربية الخاصة